Etika Normatif dan Terapan: Urgensi Etika Ilmiah, Profesi dalam Pendidikan - Vaesol Wahyu Eka Irawan (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2020)
Abstract Ethical issues are problems related to human existence in all its aspects, both as individuals and society, both in relation to God, fellow humans, and the natural environment as well as covering various fields. In relation to all that - especially between fellow humans, conflicts often arise. The conflict could result in differences in interests, as well as ideological views. However, humans as intelligent creatures always long for goodness for themselves, others and the environment. Intellect is what makes humans able to create ethics. That is the ideal value of an interpersonal and social interaction, the highest good which is used as a standard for behavior. A rule is made, the principle of goodness so that it is not only a reference for himself, but also the behavior of others. This paper generally describes theoretical ethics and practical ethics. Emphasizes the benefits, usefulness of ethics in its application to the social and state dimensions. Finally, practical social ethics is needed in a plural society to solve the various problems at hand. So that plurality is no longer a threat, but becomes the glue to enrich the literacy of social relations from various backgrounds of social groups.